2015
DOI: 10.1099/mic.0.000198
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of two major Aspergillus oryzae secreted prolyl endopeptidases able to efficiently digest proline-rich peptides of gliadin

Abstract: Prolyl endopeptidases are key enzymes in the digestion of proline-rich proteins. Fungal extracts rich in prolyl endopeptidases produced by a species such as Aspergillus oryzae used in food fermentation would be of particular interest for the development of an oral enzyme therapy product in patients affected by intolerance to gluten. Two major A. oryzae secreted prolyl endopeptidases of the MEROPS S28 peptidase family, AoS28A and AoS28B, were identified when this fungus was grown at acidic pH in a medium contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
0
12
0
1
Order By: Relevance
“…An extensive literature search was undertaken to compile high-throughput experimental studies that have characterized the secretome of Aspergillus species. A systematic search led to a comprehensive list of 46 high-throughput proteomic studies 27 73 on the secretome of 6 Aspergillus species analyzed here. Note that many high-throughput studies report proteins with transmembrane (TM) domains as part of the secretome but a few studies have specifically identified cell membrane and cell wall associated proteins along with the secretome 30 , 36 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An extensive literature search was undertaken to compile high-throughput experimental studies that have characterized the secretome of Aspergillus species. A systematic search led to a comprehensive list of 46 high-throughput proteomic studies 27 73 on the secretome of 6 Aspergillus species analyzed here. Note that many high-throughput studies report proteins with transmembrane (TM) domains as part of the secretome but a few studies have specifically identified cell membrane and cell wall associated proteins along with the secretome 30 , 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Note that many high-throughput studies report proteins with transmembrane (TM) domains as part of the secretome but a few studies have specifically identified cell membrane and cell wall associated proteins along with the secretome 30 , 36 . Our compilation of high-throughput proteomic studies led to experimentally identified lists of 437, 364, 454, 96, 469 and 171 secreted proteins in A. fumigatus 27 41 , A. flavus 30 , 42 45 , A. niger 30 , 46 58 , A. terreus 30 , 59 , 60 , A. nidulans 58 , 61 65 and A. oryzae 57 , 66 73 , respectively (Methods; Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TEPs currently used in the food industry are derived mainly from microorganisms, such as Aspergillus spp. [6][7][8][9] and Bacillus spp. [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…terreus 30,59,60 , A. nidulans 58,[61][62][63][64][65] and A. oryzae 57,[66][67][68][69][70][71][72][73] , respectively (Methods; Supplementary Table S1).…”
Section: Introductionmentioning
confidence: 99%